2021
DOI: 10.2147/opth.s293637
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Open-Angle Glaucoma with iStent Implantation Combined with Phacoemulsification in Polish Caucasian Population

Abstract: Purpose The aim of this investigation was to evaluate the impact of iStent (the first-generation trabecular bypass) implantation with phacoemulsification on the intraocular pressure (IOP) and glaucoma medication in subjects with mild to moderate open-angle glaucoma (OAG) and cataract in a Polish Caucasian population. Patients and Methods This prospective case series covered 78 eyes of (57 Polish Caucasian patients) that had undergone iStent implantation in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Another surgical method bypassing the trabecular meshwork is the iStent inject device. A prospective case series on 78 eyes evaluated the surgical outcome of iStent in combination with phacoemulsification [ 22 ]. Complete success was attained at approximately 40% after 1 year and 35.1% after 2 years, with a mean follow-up time of 21.9 months and a mean preoperative IOP of 18.4 mmHg (±3.5).…”
Section: Discussionmentioning
confidence: 99%
“…Another surgical method bypassing the trabecular meshwork is the iStent inject device. A prospective case series on 78 eyes evaluated the surgical outcome of iStent in combination with phacoemulsification [ 22 ]. Complete success was attained at approximately 40% after 1 year and 35.1% after 2 years, with a mean follow-up time of 21.9 months and a mean preoperative IOP of 18.4 mmHg (±3.5).…”
Section: Discussionmentioning
confidence: 99%
“…The technique for surgical implantation of first-generation iStent was performed as described elsewhere [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The iStent is a heparin-coated, non-ferromagnetic titanium stent that is implanted into the TM using an ab interno approach. Multiple studies have demonstrated the effectiveness of iStent at lowering IOP and medication reduction in patients undergoing cataract surgery [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This underpins the development of "blebless" procedures, or minimally invasive glaucoma surgeries (MIGS) [11]. However, a reduction in the number of complications due to improvements in surgical methods allows for earlier decision for surgical treatment, resulting in permanent and safe control IOP [12,13] Ab externo canaloplasty belongs to the group of "blebless" procedures [14], whereas iStent is included in the MIGS group [15][16][17]. The common feature of this group of procedures is the lowering of IOP by improving the physiological mechanisms of aqueous humour outflow through the conventional pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on canaloplasty have reported a promising reduction in IOP, with only a few postoperative complications [12][13][14]. The effectiveness of iStent in different populations has been described extensively [15][16][17] and has been compared to various other procedures [18][19][20][21][22]. These studies have reported a mild hypotensive effect with a clear reduction in the burden of pharmacological treatment after the procedure [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%